ANALYSIS OF THE IMPLEMENTATION OF MENTAL HEALTH POLICY AT KEDAUNG HEALTH CENTER, SUKATANI HEALTH CENTER AND LIMO HEALTH CENTER IN DEPOK CITY - Sangadji, Ekasafitri A.S; Ayuningtyas, Dumilah (UI Scholars Hub, 2021)
Mental health is one of the important indicators of health services that must be provided. Diagnosing and long-term treatment are challenges in handling mental health disorders. Puskesmas, which organizes promotive, preventive, and curative efforts, handles and improves community mental health. This study aims to determine the implementation of mental health policies in several Health Centers in Depok City. The research method uses a qualitative approach through in-depth interviews, document review by referring to the concept of policy evaluation from the Van Meter framework, and data validity using source and method triangulation. This research was conducted from October to December 2020. The results showed that several mental health implementation activities were not carried out due to the constraints of the COVID-19 pandemic situation, social restriction policies, the size and objectives of the policy were understood and had been implemented, the characteristics of the implementing agency supported the policy, the lack of availability of human resources and competence in the field of mental health, inter-organizational communication went well, the disposition of implementers was good, and there was an influence of the economic, social and political environment. The research concludes that the implementation of mental health policies has not gone well due to the COVID-19 pandemic, social restrictions, lack of human resources, and competence in mental health. It is necessary to develop SOPs that regulate the implementation of mental health during a pandemic, including mitigation efforts and coaching, training, and increasing the competence of health workers at public health centers.